2023
DOI: 10.11591/eei.v12i1.4312
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of influencing factors on pedestrian road accidents

Abstract: Road accident data includes detailed information about incidents that occurred, such as where they happened, the severity of the accident, and the number of people on the road at the time. Such information is useful in determining the causes of accidents and developing potential countermeasures. This research aims to determine the factors that contribute to pedestrian fatalities and injuries in traffic accidents. This study examined 150 pedestrian-vehicle accidents that took place between 1990 and 2021 in fort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In addition, they suffer serious injuries among all traffic participants. Other studies have shown that factors such as alcohol consumption, age or gender of drivers, lighting, road condition, pedestrian behavior, accident scene, vehicle, speed and adverse weather affect pedestrian injury rates [6][7][8][9]. Adverse weather conditions and inadequate lighting, especially of pedestrian crossings, often lead to more serious injuries on the roads [10].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they suffer serious injuries among all traffic participants. Other studies have shown that factors such as alcohol consumption, age or gender of drivers, lighting, road condition, pedestrian behavior, accident scene, vehicle, speed and adverse weather affect pedestrian injury rates [6][7][8][9]. Adverse weather conditions and inadequate lighting, especially of pedestrian crossings, often lead to more serious injuries on the roads [10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…𝑓(𝑔 𝑛7 ) = 𝑓(𝑔 1 , 𝑔 2 , 𝑔 3 , 𝑔 4 , 𝑔 5 , 𝑔 6 , 𝑔 7 , 𝑔 8 , 𝑔 9 , 𝑔 10 , 𝑔 11 ) (8) where: f(g 1 )there is snowfall, hail, above 3 mm, f(g 2 )impaired mental and physical capacity of the driver, f(g 3 )headache, f(g 4 )sleep disorder, f(g 5 )irritation, f(g 6 )nervousness, f(g 7 )cardiac arrhythmia, f(g 8 )worsening of depressive symptoms. f(g 9 )sluggishness, f(g 10 )fatigue, f(g 11 )suffocation.…”
Section: Weather Conditions Acronymsmentioning
confidence: 99%
“…This setting offers a chance for scholars studying power systems, energy markets, and emerging breakthroughs in AI to collaborate. Intelligent systems and artificial intelligence (AI) have the potential to be strong tools for developing novel computer-related solutions planning, execution, maintaining, market surveillance, and risk management [13]. Intelligent systems are ideal decision-support tools.…”
Section: Economy and Artificial Intelligencementioning
confidence: 99%
“…For transportation experts and politicians, this paper provides as an introduction to AV technology, its possible effects, and challenges. [3] By preventing fatal collisions, giving the elderly and disabled essential mobility, expanding road capacity, conserving fuel, and reducing emissions, AVs have the ability to drastically revolutionize current transportation systems. Vehicles may become an on-demand service as a result of developments in shared transportation and ownership that are complementary.…”
Section: Inroductionmentioning
confidence: 99%